On the systematics of asteroseismological mass determinations of PG 1159 stars - Althaus, Leandro Gabriel (2008)
Aims. We analyze systematics in the asteroseismological mass determination methods in pulsating PG 1159 stars. Methods. We compare the seismic masses resulting from the comparison of the observed mean period spacings with the usually adopted asymptotic period spacings, ∆Πa , and the average of the computed period spacings, ∆Π . Computations are based on full PG 1159 evolutionary models with stellar masses ranging from 0.530 to 0.741 M which take into account the complete evolution of progenitor stars. Results. We conclude that asteroseismology is a precise and powerful technique which determines the masses to a high internal accuracy, but it depends on the adopted mass determination method. In particular, we find that in the case of pulsating PG 1159 stars characterized by short pulsation periods, such as PG 2131+066 and PG 0122+200, the employment of the asymptotic period spacings overestimates the stellar mass by about 0.06 M as compared with inferences from the average of the period spacings. In this case, the discrepancy between asteroseismological and spectroscopical masses is markedly reduced when use is made of the mean period spacing ∆Π instead of the asymptotic period spacing ∆Πa .